Double-antigen sandwich ELISA based on chimeric antigens for detection of antibodies to Trypanosoma cruzi in human sera. - Natália Erdens Maron Freitas; Emily Ferreira Santos; Leonardo Maia Leony; Ângelo Antônio Oliveira Silva; Ramona Tavares Daltro; Larissa de Carvalho Medrado Vasconcelos; Gabriela Agra Duarte; Cristiane Oliveira da Mota; Edimilson Domingos Silva; Paola Alejandra Fiorani Celedon; Nilson Ivo Tonin Zanchin; Fred Luciano Neves Santos (Public Library of Science (PLoS), 2022)
Background Enzyme-linked immunosorbent assays (ELISA) are generally the chosen test for Chagas disease (CD) diagnosis; however, its performance depends on the antigen preparation adsorbed to the solid phase, which may lead to false-positive results and cross-reactions. The use of chimeric recombinant antigens can overcome this limitation. Four chimeric antigens from Trypanosoma cruzi (IBMP-8.1, IBMP-8.2, IBMP-8.3 and IBMP-8.4) were developed and evaluated in phase I, II and III studies using indirect ELISA as diagnostic platform. However, peroxidase-labeled secondary anti-human IgG antibody, which is employed in indirect ELISAs, limits its use for the detection of species-specific and class-specific antibodies. To overcome this limitation, peroxidase-labeled antigens can be utilized, diagnosing both acute or chronic infection, in a species and immunoglobulin class-independent manner, through the use of a double-antigen sandwich ELISA (DAgS-ELISA). We aimed to evaluate and validate the diagnostic performance of the chimeric antigens IBMP-8.1, IBMP-8.2, IBMP-8.3 and IBMP-8.4 in the DAgS-ELISA platform. Methodology/principal findings DAgS-ELISA was optimized by checkerboard titration. In phase I study, 207 positive and 205 negative samples were evaluated. Cross-reactivity to other infections was also assessed using 68 samples. The selected conditions for the tests utilized 25 ng of antigen per well and the conjugate diluted at 1:2,000 for all molecules. In the phase I study, the areas under the curve of IBMP-8.1, IBMP-8.2, IBMP-8.3 and IBMP-8.4 were 98.7%, 99.5%, 98.6% and 98.8%, respectively. Among the positive samples, IBMP-8.1 antigen classified 53 (25.6%) as false negative, IBMP-8.2, 27 (13%), IBMP-8.3, 24 (11.6%) and IBMP-8.4, 43 (20.8%), giving sensitivities of 74.4%, 87%, 88.4% and 79.2%, respectively. The only antigen that did not reach 100% specificity was IBMP-8.3, with 96.6%. IBMP-8.3 was also the only molecule to show cross-reactivity with HTLV. Conclusions/significance DAgS-ELISA is a promising tool for immunodiagnosis, and despite the high AUC values, the performance of this assay was different from the values obtained by our group when using these antigens in the indirect ELISA, for this reason, improvements are being considered to increase the sensitivity of the DAgS-ELISA.